Association Between Cigarette Package Warning Messages, Self-Efficacy, and Smoking Behavior among Students at Health Polytechnic in Surakarta, Indonesia - Roy Romey Daulas Mangunsong; Bhisma Murti; Mahendra Wijaya (Masters Program in Public Health, Sebelas Maret University, 2016)
Background: Total number of smokers around the worldwide is approximately 140 million. The number of deaths caused by tobacco smoking related diseases is approximately 300,000 per year. Average age to start smoking is 17.6 years. The high number of smokers at young age indicates that public awareness of the dangers of smoking is still very low. This study aimed to determine the association between cigarette package warning messages, self-efficacy, and smoking behavior among students.Subject and Methods: This was an analytical observational study with cross sectional design, carried out in Surakarta, Indonesia. A total of 71 students at Polytechnic of health and sciences were selected by using random sampling technique. The dependent variable was smoking behavior. The independent variables were illustrated the dangers of cigarette smoking advertising and self-efficacy. The data was collected by questionnaire and analyzed by using regression logistic.Results: there is a relationship between an ad illustrated the dangers of cigarette smoking with smoking behavior (OR= 2.87; 95% CI= 0.91 to 9.03; p = 0.071). There is a relationship between the smoking behavior of yourself with the efficacy (OR = 0.23; 95% CI= 0.07 to 0.74; p = 0.013). The ads illustrated the dangers of cigarette smoking and self-efficacy was able to explain the smoking behavior of 16.2% and amounted to 83.8% explained by factors other than the research model.Conclusion: there is a connection between the ads illustrated the dangers of cigarette smoking and the smoking behavior of self-efficacy with the students.Keywords: cigarette package warning messages, self-efficacy, smoking behaviorCorrespondence: Roy Romey Daulas Mangunsong. Department of Speech and Occupational Therapy, Health Polytechnic Surakarta. Email: Surakartaroypoltekstw@gmail.comJournal of Health Policy and Management (2016), 1(1): 44-52https://doi.org/10.26911/thejhpm.2016.01.01.07